Cover Image, Volume 49, Issue 2. (15th February 2018) - Talò, G.; Turrisi, C.; Arrigoni, C.; Recordati, C.; Gerges, I.; Tamplenizza, M.; Cappelluti, A.; Riboldi, S.A.; Moretti, M.
Abstract : The cover image, by G. Talò et al., is based on the Research Article Industrialization of a perfusion bioreactor: Prime example of a non‐straightforward process, DOI: 10.1002/term.2480 . This work was partially funded by POR FESR 2007–2013 resources (grant ID: ATP 2009, No. 13396272".